Hedging Commodity Price Risk Exposure and the Financial Performance of Manufacturing Companies in Kenya (African Multidisciplinary Journal of Research, 2022)
This study sought to establish how the commodity price exposure faced by manufacturing companies in Kenya influence their financial performance focusing on the earnings before interest and tax (EBIT) and return on assets (ROA). The objective of the study focused on whether commodity price risk exposure should compel manufacturing entities to use hedging strategies based on the premise that commodity risk exposure affects the financial performance. The key theory upon which the research was grounded is the game theory given that irrespective of whether the players act independently or in a group and given that there is more than one course of action, the outcome of the “game” is dependent on the interface of pursued strategies. The researcher conducted a thorough literature review focusing on the key variables of the study. The literature reviewed was critical in providing different perspectives and aspects of commodity price risk exposure and its management strategies. The study adopted an analytical research design in order to get a better understanding of the impact of the independent variables on the dependent variable. The target population consisted of all manufacturing companies in Kenya from which a representative sample of two hundred and fifty five companies was selected through stratified sampling from the key sectors as classified by the Kenya Association of Manufacturers (KAM). The study used ten year panel data given that this period was deemed to be adequate for an objective analysis. Data was collected from archival financial statements to compute the key measures under the independent and dependent variables. Data analysis was done through a general linear model for panel data analysis. From the results obtained, it was observed that manufacturing firms do not disclose any derivative usage in their financial statements. Under the EBITS model, it was observed that TITS was statistically significant and points to the need to hedge commodity price risk in order to enhance financial performance. Under the ROA model, it was observed that Lnassets and CFTA were statistically significant and points to the need maintain adequate cash flows to hedge commodity price risk in order to enhance financial performance.Keywords: Hedging, Commodity, Price Risk Exposure, Financial, Performance, Manufacturing Companies